Improving oral hygiene skills by computer-based training : A randomized controlled comparison of the modified bass and the fones techniques - Harnacke, Daniela; Mitter, Simona; Lehner, Marc; Munzert, Jörn; Deinzer, Renate; Justus Liebig University Giessen (My University, 2012)
Background: Gingivitis and other plaque-associated diseases have a high prevalence in western communities even though the majority of adults report daily oral hygiene. This indicates a lack of oral hygiene skills. Currently, there is no clear evidence as to which brushing technique would bring about the best oral hygiene skills. While the modified Bass technique is often recommended by dentists and in textbooks, the Fones technique is often recommended in patient brochures. Still, standardized comparisons of the effectiveness of teaching these techniques are lacking. Methodology/Principal Findings: In a final sample of n=56 students, this multidisciplinary, randomized, examiner-blinded, controlled study compared the effects of parallel and standardized interactive computer presentations teaching either the Fones or the modified Bass technique. A control group was taught the basics of tooth brushing alone. Oral hygiene skills (remaining plaque after thorough oral hygiene) and gingivitis were assessed at baseline and 6, 12, and 28 weeks after the intervention. We found a significant group×time interaction for gingivitis (F(4/102)=3.267; p=0.016; e=0.957; ?2=0.114) and a significant main effect of group for oral hygiene skills (F(2/51)=7.088; p=0.002; ?2=0.218). Fones was superior to Bass; Bass did not differ from the control group. Group differences were most prominent after 6 and 12 weeks. Conclusions/Significance: The present trial indicates an advantage of teaching the Fones as compared to the modified Bass technique with respect to oral hygiene skills and gingivitis. Future studies are needed to analyze whether the disadvantage of teaching the Bass technique observed here is restricted to the teaching method employed. Trial Registration: German Clinical Trials Register http://www.drks.de/DRKS00003488
Keywords: lack of oral hygiene skills; modified Bass technique; Fones technique; interactive computer presentations teaching; clinical trial; ddc:610